Association Between Sleep Quality, Musculoskeletal Pain and Physical and Psychosocial Well-Being Among Employees Working from Home: Life Sciences-Physiotherapy - Kanishka; Manish, Kumar; Tewatia, Sumit (International Journal of Life Science and Pharma Research, 2022)
COVID-19 has perplexed the world into an unexpected state of affairs. With the implementation of nationwide lockdown, people have begun to ‘Work for Home’ in many employment sectors. Though the policy has managed to keep people safe from the devastating effects of the virus, it has, however, imposed most employees into a sedentary lifestyle. The current situation has resulted in disordered sleep, musculoskeletal pain, physical and psychosocial well-being decline due to irregular work hours, and mental health issues due to corona phobia. The current study aims to find the correlation between sleep duration, musculoskeletal pain, and physical and psychosocial well-being in employees working from home during the COVID-19 pandemic lockdown. One hundred fifty-three samples from the North India region were studied in a correlation study. Subjects working from home for at least one month or more and only due to COVID-19 lockdown were excluded, while those with any musculoskeletal, cardiovascular or neurological disorder were excluded. Questionnaires employed were Pittsburg Sleep Quality Index (PSQI) (for sleep quality), Chronic Pain Grade Questionnaire (CPGQ) (for pain intensity), and Short Form-12 (SF-12) Questionnaire (for physical and psychosocial well-being). Scores were calculated, and Pearson’s correlation was found. One hundred fifty-three samples (mean age= 32.73±5.55, mean height=167±9.22, mean weight=67.2±13.7, mean BMI=23.9±3.97) were evaluated, which revealed a higher negative correlation coefficient value between MSK pain intensity and PCS value (-0.535) describing that the pain increased with deterioration in sleep, and sleep quality and MCS value (-0.423) stating that the psychosocial well-being worsened with the decline in sleep quality; while a highly positive correlation was established with the sleep quality and pain intensity scores (0.420) depicting that pain degraded the physical well-being. A weak correlation was reported in the relationship between the intensity of MSK pain with sleep quality (-0.218) and PCS score (-0.323), suggesting no significant impact (significant at the 0.01 level (2-tailed). A significant correlation has been established between sleep quality, the intensity of musculoskeletal pain, and the physical and psychosocial well-being of employees working from home during the COVID-19 pandemic lockdown.